Economic size trumps all else? Lessons from BRICSAM - Cooper, Andrew F. (The Centre for International Governance Innovation WaterlooCA, 2006)
Questions whether size (economic or population) of emerging economies alone is enough to warrant accomodation in the rules and structures of the international system. Observes the economic and social trends of these countries, and their upwards aspirations towards the top-tier of the global architecture.